A Comprehensive Understanding of Vidhura Marma. - Gopal, Uma B; Kamalashree, K M (International Research Journal of Ayurveda & Yoga, 2023)
The concept of Marma is one of the unique principle mentioned in ancient Ayurvedic texts. Marmaisvital area in the body where there is conglomeration of Mamsa, Sira, Snayu, Asthi andSandhi. In these area Prana resides specifically and is more vulnerable. These generate the symptoms from excruciating pain to fatal effect when exposed to trauma. Acharya’shave mentioned 107 such vital areas in the body. Vidhura Marma is one among them, present in the head region, postero-inferior to the Ear within half angula dimension. It is a Vaikalyakara Marma and on injury leads to Baadhirya (Hearing impairment). Knowledge of Marma has said to cover half of the jurisdiction of Shalya Tantra. Hence, clear knowledge of Marma is very important in clinical field in preventing the complications during the surgical and Para surgical procedures. Details are collected from ayurvedic texts and published papers aiming to provide a comprehensive overview on Vidhura Marma.